2007
DOI: 10.1113/jphysiol.2006.126474
|View full text |Cite
|
Sign up to set email alerts
|

Role of calsequestrin evaluated from changes in free and total calcium concentrations in the sarcoplasmic reticulum of frog cut skeletal muscle fibres

Abstract: Calsequestrin is a large-capacity Ca-binding protein located in the terminal cisternae of sarcoplasmic reticulum (SR) suggesting a role as a buffer of the concentration of free Ca in the SR ( Calsequestrin is a high-capacity Ca binding protein located in the terminal cisternae of the sarcoplasmic reticulum (SR) of skeletal muscle (MacLennan & Wong, 1971). One function proposed for calsequestrin is that it rapidly buffers [Ca 2+ ] in the sarcoplasmic reticulum (denoted [Ca 2+ ] SR ). In this way, local dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 48 publications
(155 reference statements)
10
44
0
Order By: Relevance
“…In contrast, use of TMX, the other purpurate indicator in Table 1, is problematic because TMX has a significant membrane permeability (Ogawa et al, 1980; Ohnishi, 1979). In both cut and intact fibres, the ΔA signal from TMX is biphasic, with an early component that monitors Δ[Ca 2+ ] and a later component (of opposite sign) that appears to reflect a decrease in [Ca 2+ ] within the SR lumen (Maylie et al, 1987a; Pape et al, 2007). Because the time courses of the two TMX components overlap, estimation of the Δ[Ca 2+ ] waveform from the ΔA of TMX is problematic.…”
Section: Comparison Of Ca2+ Signals From Furaptra and Other Low-amentioning
confidence: 99%
“…In contrast, use of TMX, the other purpurate indicator in Table 1, is problematic because TMX has a significant membrane permeability (Ogawa et al, 1980; Ohnishi, 1979). In both cut and intact fibres, the ΔA signal from TMX is biphasic, with an early component that monitors Δ[Ca 2+ ] and a later component (of opposite sign) that appears to reflect a decrease in [Ca 2+ ] within the SR lumen (Maylie et al, 1987a; Pape et al, 2007). Because the time courses of the two TMX components overlap, estimation of the Δ[Ca 2+ ] waveform from the ΔA of TMX is problematic.…”
Section: Comparison Of Ca2+ Signals From Furaptra and Other Low-amentioning
confidence: 99%
“…Given that Casq1 provides much of the calcium that signals muscle contraction (25,26), the buffering features found in solution should transfer to the storage properties of the SR in cells. Indeed, strongly cooperative calcium buffering by the SR was first documented by Pape et al (31), who showed with frog muscle that the calcium buffering power of the empty SR is negligible compared with the value at rest, a property they attributed to calsequestrin. Working on mouse muscle, Royer et al (19) confirmed the attribution, quantified the contribution by Casq1 at 75% of released calcium (26), and equated it to the hump of calcium flux caused by a large depolarization (19).…”
Section: Calsequestrin Undergoes Major Conformational Changes Upon Camentioning
confidence: 99%
“…In particular, experiments on multicellular cardiac preparations strongly suggest that contribution of SR Ca 2ϩ release to e-c coupling of the fish heart is significantly less than SL Ca 2ϩ entry, because in the majority of fish species examined, the force of cardiac contraction is weakly responsive to Ry. At physiological heart rates and temperatures, Ry inhibition of cardiac contraction varies from 0 to 32% (2,12,14,33,49), the most notable exceptions being tuna and an eurythermic neotropical teleost, Synbranchus marmarotus (28, 37), species in which Ry inhibition of force generation ranges from 30 to 53%.On the other hand, it has been found that in cardiac myocytes of rainbow trout, caffeine-releasable Ca 2ϩ stores are massive, almost an order of magnitude larger than in mammalian cardiac myocytes and approaching to the values of the mammalian skeletal muscle fibers (26,35,45). Thus, there is a striking mismatch between massive SR Ca 2ϩ stores and relatively weak effect of Ry on cardiac contraction at least for the trout heart (2,22,33,46), which still lacks a mechanistic explanation and raises several questions.…”
mentioning
confidence: 96%
“…On the other hand, it has been found that in cardiac myocytes of rainbow trout, caffeine-releasable Ca 2ϩ stores are massive, almost an order of magnitude larger than in mammalian cardiac myocytes and approaching to the values of the mammalian skeletal muscle fibers (26,35,45). Thus, there is a striking mismatch between massive SR Ca 2ϩ stores and relatively weak effect of Ry on cardiac contraction at least for the trout heart (2,22,33,46), which still lacks a mechanistic explanation and raises several questions.…”
mentioning
confidence: 98%